UPLC-HRMS-MS profiling of Ludwigia adscendens subsp. diffusa aerial parts and investigation of the anti-inflammatory effect - Enas M. Shawky; Rim Hamdy; Mohamed R. Elgindi; Mostafa H. Baky (Scientific Reports)
Abstract Ludwigia adscendens subsp. diffusa (Forssk.) P.H. Raven, also known as L. stolonifera, is an aquatic herb belonging to family Onagraceae and widely distributed in canals and drains in the Nile Delta, Egypt. The main goal of the current study is to investigate the metabolic profile of L. adscendens aerial parts using ultra-high performance liquid chromatography coupled with high resolution mass spectrometry (UPLC-HRMS/MS) and investigation of its anti-inflammatory activity. A total of 168 metabolites were identified by UPLC-MS/MS analysis in negative and positive modes belonging to several phytochemical classes including phenolics (57), flavonoids (26), terpenoids (25), sterols (23), fatty acids (11), coumarins (7) organic acids (5), sugar derivatives (5), lactones (4), acids (3), and glycoside (2). The UPLC-MS analysis of L. adscendens revealed identification of a diverse array of phytochemicals which contribute to its potential pharmacological properties. The identification of bioactive metabolites in L. adscendens aerial parts including gallic acid, quercetin, ellagic acid, and betulinic acid can impart biological activities including antioxidant and anti-inflammatory activities. The anti-inflammatory activity was investigated for L. adscendens methanol and ethyl acetate extract using nitric acid inhibition assay revealing IC50 of 26.4 and 23.9 µg/ml, respectively, compared to resveratrol as a standard anti-inflammatory with IC50 value of 14.2 µg/ml. These findings can highlight the importance of L. adscendens aerial parts as a potential source of bioactive metabolites.